What are your thoughts? Exploring age-related changes in episodic and semantic autobiographical content on an open-ended retrieval task. Issue 10 (26th November 2021) - Strikwerda-Brown, Cherie; Williams, Kayla; Lévesque, Marianne; Brambati, Simona; Sheldon, Signy
ABSTRACT: Older adults display impairments in accessing episodic, but not semantic details, when specifically requested to construct autobiographical events. How aging affects access to autobiographical information under conditions of low retrieval constraint remains unclear. We examined the production of episodic and "non-episodic" details in young ( n  = 25) and older ( n  = 24) adults on a novel autobiographical narrative task free from constraints on the type of information to be retrieved (Thoughts task), compared with the standard autobiographical memory and picture description tasks. Older adults generated fewer episodic and more non-episodic details on the memory task than young adults, however there was no age difference in detail profiles on the Thoughts task. Under these conditions of low retrieval constraint, narratives of young and older adults consisted of mostly personal and general semantic content. Young adults also provided less episodic and more semantic details on the Thoughts than the memory task, while older adults provided similar amounts of details across tasks. These results reveal that both young and older adults retrieve semantic autobiographical content under minimally constrained retrieval conditions. Moreover, aging may impact upon the ability to shift the detail types (episodic, semantic) provided in response to changing demands of different autobiographical narrative tasks.